Reduced levels of potential circulating biomarkers of cardiovascular diseases in apparently healthy vegetarian men - Navarro, Julio Acosta; de Gouveia, Luiza Antoniazzi; Rocha-Penha, Lilliam [UNESP]; Cinegaglia, Naiara [UNESP]; Belo, Vanessa; Castro, Michele Mazzaron de; Sandrim, Valeria Cristina [UNESP] (Elsevier, 2016)
Background Several evidences report that a vegetarian diet is protector against cardiovascular diseases. Few studies have demonstrated the circulating profile of cardiovascular biomarkers in vegetarians. Therefore, the aims of the current study were compared the plasma concentrations of myeloperoxidase (MPO), metalloproteinase (MMP)-9, MMP-2, tissue inhibitor of MMP (TIMP)-1 and TIMP-2 between healthy vegetarian (Veg) and healthy omnivorous (Omn). Methods Using ELISA and multiplexed bead immunoassay, we measured in plasma from 43 Veg and 41 Omn the cardiovascular biomarkers concentrations cited above. Results We found significant lower concentrations of MPO, MMP-9, MMP-2 and MMP-9/TIMP-1 ratio in Veg compared to Omn (all P < 0.05). Moreover, MMP-9 concentrations were correlated positively with leukocytes and neutrophils count in both groups (all P < 0.05). Conclusion A vegetarian diet is associated with a healthier profile of cardiovascular biomarkers compared to omnivorous.
Keywords: Cardiovascular biomarkers; MMP-2; MMP-9; MPO; Omnivorous; TIMP; Vegetarians